2019
DOI: 10.7150/thno.35737
|View full text |Cite
|
Sign up to set email alerts
|

miR-27a regulates vascular remodeling by targeting endothelial cells' apoptosis and interaction with vascular smooth muscle cells in aortic dissection

Abstract: Rationale: Aortic dissection (AD) is caused by functional disorder of cells in the aortic wall, which is largely attributed to vascular remodeling. Therapeutic strategies for AD remain limited due to our incomplete understanding of the role of endothelial cells (ECs) in AD pathogenesis. This study aimed to identify the regulatory role of miR-27a in AD and provide a mechanistic basis for a non-invasive treatment of AD.Methods: We harvested aortas from normal and AD patients to explore the expression of miR-27a.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…A recent study showed that upregulated expression of Fas-associated protein with death domain (FADD) and activation of the apoptosis pathway led to downregulation of miR-27a and induction of apoptosis in endothelial cells (ECs). Then, aortic dissection was induced through promotion of VSMC migration by ECs after downregulation of miR-27a (43).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that upregulated expression of Fas-associated protein with death domain (FADD) and activation of the apoptosis pathway led to downregulation of miR-27a and induction of apoptosis in endothelial cells (ECs). Then, aortic dissection was induced through promotion of VSMC migration by ECs after downregulation of miR-27a (43).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some studies revealed the regulatory roles of microRNAs on endothelial cells behaviour during aortic dissection. For example, miR‐27a promotes the activation of apoptotic pathway by targeting the expression of fas‐associated protein with death domain (FADD), thereby promoting the apoptosis of EC, whereas the treatment of miR‐27a activator targeting ECs apoptosis can significantly reduce the incidence of AD 42 . Together, these evidences provide us with new insights into the occurrence and development of AD, and suggest more comprehensive prevention and diagnostic methods.…”
Section: The Pathogenesis Of Admentioning
confidence: 99%
“…MiRNAs are closely associated with the AAA pathogenic mechanism [61]. In AAA patients, miRNAs affect the pathogenesis of AAAs by forming networks to regulate the ECM turnover, MMP family, different inflammatory components, and vascular smooth muscle development [62][63][64][65].…”
Section: Mirnas In Aaasmentioning
confidence: 99%